2016
DOI: 10.31018/jans.v8i2.886
|View full text |Cite
|
Sign up to set email alerts
|

Mungbean yield and nutrient uptake performance in response of NPK and lime levels under acid soil in Vindhyan region, India

Abstract: A field experiment was conducted to understanding the management of soil acidity with NPK and lime levels for sustainable mungbean productivity, Crop was sown during kharif season of 2014at Agronomy farm of Rajiv Gandhi South Campus Banaras Hindu University, Barkachha, Mirzapur, Uttar Pradesh. Results of the study demonstrated that significant improvement in seed (524 kg /ha), straw (1426 kg /ha), biological yield (1949 kg/ha) and total NPK uptake (96.68 kg/ha) were recorded in 100% RDF. Similar results were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The residual effect of lime and organic manure application was more pronounced in the third crop, mungbean. Our results demonstrated that residual effect of combined application of lime and organic manure significantly increased seed yield (Table 2), and nutrient content and uptake (Table 3) of mungbean, which is in line with previous experimental results [8,[73][74][75]. Kasa et al [76] found that application of different level of lime and phosphorus significantly increased the yield and yield contributing characters of Haricot bean in Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…The residual effect of lime and organic manure application was more pronounced in the third crop, mungbean. Our results demonstrated that residual effect of combined application of lime and organic manure significantly increased seed yield (Table 2), and nutrient content and uptake (Table 3) of mungbean, which is in line with previous experimental results [8,[73][74][75]. Kasa et al [76] found that application of different level of lime and phosphorus significantly increased the yield and yield contributing characters of Haricot bean in Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…Many other intercropping systems were also reported by several workers (Ahlawat et al, 2005;Kumar et al, 2006Kumar et al, , 2008Kumar et al, , and 2010a. Studies have demonstrated synergistic effects of urdbean and mungbean on sugarcane yields in spring-planted crops, resulting in an additional yield of 0.4-0.5 tonnes per hectare for these pulses (Lal et al, 1999;Varma and Meena, 2016).…”
Section: Pulses For Improving Crop Productivity and Profitability In Camentioning
confidence: 99%
“…Nitrogen is an important component of chlorophyll and which is essential for various enzyme activities in order for plants to develop properly. The proper quantity of phosphorus can help the crop to produce more pods while simultaneously developing healthier stocks and root systems [11].…”
Section: Yield Of Greengrammentioning
confidence: 99%